The nomogram of contrast-enhanced ultrasound-targeted fusion biopsy predicts the pathology upgrade in prostate cancer - Cao, Jianhui; Feng, Bin; Zheng, Junbiao (Frontiers in Oncology, 2025)
AimThe aim of this study was to analyze the consistency between the pathology of combined systematic and contrast-enhanced ultrasound (CEUS)-targeted prostate biopsy and radical prostatectomy (RP) by building a nomogram to predict the pathology upgrade of Gleason grade group (GGG).MethodsA total of 113 participants with prostate cancer with combined systematic and CEUS-targeted prostate biopsy followed by RP were recruited between January 2021 and November 2024. The Kappa coefficient of pre- and post-RP GGG was calculated. The independent predictors for pathology upgrade were screened using logistic regression and then applied to build a nomogram for pathology upgrade prediction. The performance of the nomogram was assessed by receiver operating characteristic analysis, calibration curve analysis, and decision curve analysis.ResultAmong 113 participants, 25 (22.1%) Gleason grade group upgrading (GGGU) and 88 (77.9%) non-GGGU cases were found. Moderate consistency of prostate cancer GGG between combined systematic and CEUS-targeted prostate biopsy and final RP pathology was found (Kappa = 0.46, p < 0.01). The primary biopsy Gleason Score [odds ratio (OR) = 0.22, p < 0.01] and the greatest percentage of cancer in a single core (OR = 1.04, p < 0.01) were independent predictors for post-RP GGGU. The area under the curve of the established nomogram reached 0.83, and the calibration curve showed a robust result.ConclusionThe nomogram integrating CEUS-targeted fusion biopsy variables effectively predicted the risk of pathology upgrade in prostate cancer, which showed potential to guide clinicians in optimizing surgical management in patients with prostate cancer.